2015
DOI: 10.1159/000369354
|View full text |Cite
|
Sign up to set email alerts
|

Using the Accelerometers Integrated in Smartphones to Evaluate Essential Tremor

Abstract: Background/Aims: Evaluation of tremor constitutes a crucial step from the diagnosis to the initial treatment and follow-up of patients with essential tremor. The severity of tremor can be evaluated using clinical rating scales, accelerometry, or electrophysiology. Clinical scores are subjectively given, may be affected by intra- and interevaluator variations due to different experience, delays between consultations, and subtle changes in tremor severity. Existing medical devices are not routinely used: they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Accelerometers have been applied outside the operating room (OR) for a wide variety of purposes, e.g., to characterize pathological tremor [8,13], to compare it with physiological tremor [20,35,36], and to evaluate the severity and evolution of tremor [28,29,40] and the tremor-alleviating effect of drugs or DBS [22,36,47]. Pulliam et al [34] used motion sensors during postoperative DBS pulse generator programming to develop automated programming algorithms and concluded that objective assessment can improve patients' outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers have been applied outside the operating room (OR) for a wide variety of purposes, e.g., to characterize pathological tremor [8,13], to compare it with physiological tremor [20,35,36], and to evaluate the severity and evolution of tremor [28,29,40] and the tremor-alleviating effect of drugs or DBS [22,36,47]. Pulliam et al [34] used motion sensors during postoperative DBS pulse generator programming to develop automated programming algorithms and concluded that objective assessment can improve patients' outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers and gyroscopes are used commonly in the assessment of hand tremor, but there are only a few published studies in which accelerometry was used to assess head tremor and no reports in which gyroscopes were used. In general, body motion has six degrees of freedom: three‐dimensional (3D) translation and 3D rotation.…”
mentioning
confidence: 99%
“…The Georgia Tech Research Institute developed iTrem, but regulatory issues by the Food and Drug Administration (FDA) prevent the release of the app [13]. Senova et al [4] reported on Itremor, which also does not provide researchers with the raw data, but instead with a few calculated statistics (like acceleration, frequency, and magnitude). The app is only available from Ad Hoc distribution, not from the App Store.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative features can be extracted from the motion sensors on the device and used to develop mathematical models for predicting rating scores from kinematic data [3]. Accelerometers integrated in smartphones or wrist-worn devices can also be used for this purpose [4], which lowers the threshold for tremor quantification during activities of daily living.…”
Section: Introductionmentioning
confidence: 99%